The effect of play therapy as a therapeutic communication on social interactions of Children with Special Needs - Zikri Fachrul Nurhadi; Rosanti Utami Dewi; Syaidah Nurhalimah (Universitas Padjadjaran, 2021)
Therapeutic communication is one of the communications applied to Children with Special Needs (CSN), designed for therapy. This research is triggered by the number of Children with Special Needs who have not been accommodated to receive a complete education; this means Children with Special Needs have not been able to get an education because of various problems such as school places, parents inability, and the unwillingness of parents to let their children study which is influenced by social difficulties. Children with Special Needs typically feel scared, reluctant, hesitant, or unable to express themselves; these children are often excluded because they cannot communicate and socialize well, so that the impact is not good for the psychic, mental, social, and sensory of the children. This study aims to analyze the effect of empathy and warmth on associative and dissociative social processes. The research uses a study type with a quantitative approach with 50 people as samples. Data collection is carried out through primary data collection by using a questionnaire spread to several respondents and field observation to see the therapy used. The results showed that the empathy correlation coefficient value of the associative social process was 0.443 (strong enough), and the dissociative social process was 0.554 (strong enough). Meanwhile, the value of the warmth coefficient correlation to the associative social process was 0.850 (strong), and the dissociative social process was 0.880 (strong). Thus, the effect of play therapy as a therapeutic communication on social interaction is 0.428 (strong enough), while the achievement coefficient of determination is 0.283. The independent variables have an influence and contribute with a rate of 28.3% to the independent variable.